The Role of Structural Imperfections in Sr2FeMoO6 Thin Films - Saloaro, Minnamari (fi=Turun yliopisto|en=University of Turku|, 2015)
In this work, Sr2FeMoO6 (SFMO) thin films were studied with the main focus on their magnetic and magneto-transport properties. The fabrication process of pulsed laser deposited SFMO films was first optimized. Then the effects of strain, film thickness and substrate were thoroughly investigated. In addition to these external factors, the effect of intrinsic defects on the magnetic properties of SFMO were also clarified. Secondly, the magnetoresistivity mechanims of SFMO films were studied and a semiempirical model of the temperature dependence of resistivity was introduced. The films were grown on single crystal substrates using a ceramic target made with sol-gel method. The structural characterization of the films were carried out with X-ray diffraction, atomic force microscopy, transmission electron microscopy and high kinetic energy photoelectron spectroscopy. The magnetic properties were measured with SQUID magnetometer and the magneto-transport properties by magnetometer with a resistivity option. SFMO films with the best combination of structural and magnetic properties were grown in Ar atmosphere at 1050 °C . Their magnetic properties could not be improved by the ex situ post-annealing treatments aside from the treatments in ultra-high vacuum conditions. The optimal film thickness was found to be around 150 nm and only small improvement in the magnetic properties with decreasing strain was observed. Instead, the magnetic properties were observed to be highly dependent on the choice of the substrate due to the lattice mismatch induced defects, which are best avoided by using the SrTiO3 substrate. The large difference in the Curie temperature and the saturation magnetization between the SFMO thin film and polycrystalline bulk samples was connected to the antisite disorder and oxygen vacancies. Thus, the Curie temperature of SFMO thin films could be improved by increasing the amount of oxygen vacancies for example with ultra-high vacuum treatments or improving the B-site ordering by further optimization of the deposition parameters. The magneto-transport properties of SFMO thin films do not follow any conventional models, but the temperature dependence of resistivity was succesfully described with a model of two spin channel system. Also, evidences that the resistivity-temperature behaviour of SFMO thin films is dominated by the structural defects, which reduce the band gap in the majority spin band were found. Moreover, the magnetic field response of the resistivity in SFMO thin films were found to be superposition of different mechanisms that seems to be related to the structural changes in the film.

Tässä työssä keskityttiin Sr2FeMoO6 (SFMO) ohutkalvojen tutkimukseen pääpainon ollessa niiden magneettisissa ominaisuuksissa ja magneettikentästä riippuvissa virrankuljetusominaisuuksissa. Laserhöyrystyksellä tehtyjen SFMO ohutkalvojen valmistusprosessi optimoitiin, jonka jälkeen venytyksen, kalvon paksuuden ja kasvatusalustan vaikutus tutkittiin huolellisesti. Näiden ulkoisten tekijöiden lisäksi, kalvon sisäisten virheiden vaikutusta sen magneettisiin ominaisuuksiin selvennettiin. Toisaalta työssä tarkasteltiin myös SFMO ohutkalvojen magnetoresistiivisyysominaisuuksia ja esiteltiin puoliempiirinen malli resistiivisyyden lämpötilariippuvuudelle. SFMO kalvot kasvatettiin yksittäiskidealustoille käyttäen sooli-geeli menetelmällä valmistettua keraamista kohtiota. Rakenteellinen karakterisointi suoritettiin röntgendiffraktiolla, atomivoimamikroskopialla, läpäisyelektronimikroskopialla ja korkean kineettisen energian fotoelektronispektroskopialla. Magneettiset ominaisuudet mitattiin SQUID-magnetometrillä ja virrankuljetus ominaisuudet magneettikentässä magnetometrillä, jossa on resistiivisyys optio. Parhaat SFMO ohutkalvot kasvatettiin Ar kaasukehässä 1050 °C lämpötilassa. Niiden magneettisia ominaisuuksia ei kyetty parantamaan kasvatuksen jälkeisillä lämpökäsittelyillä lukuunottamatta käsittelyä ultravakuumiolosuhteissa. Optimaaliseksi kalvon paksuudeksi saatiin noin 150 nm ja venymän havaittiin vaikuttavan magneettisiin ominaisuuksiin vain vähän. Sen sijaan, magneettisten ominaisuuksien havaittiin olevan vahvasti riippuvaisia kasvatusalustasta hilojen yhteensopimattomuuden aiheuttamien kidevirheiden takia, jotka voidaan parhaiten välttää käyttämällä SrTiO3 alustaa. Ohutkalvojen ja monikiteisten bulkki näytteiden välillä olevan suuren eron Curien lämpötilassa ja saturaatiomagnetisaatiossa havaittiin liittyvän Fe/Mo-epäjärjestyksen ja happivakanssien määrään. Näin ollen SFMO ohutkalvojen Curien lämpötilaa voidaan parantaa kasvattamalla happivakanssien määrää esimerkiksi ultravakuumikäsittelyllä tai parantamalla Fe/Mo-järjestystä optimoimalla kasvatusparametrejä edelleen. SFMO ohutkalvojen magneettikentästä riippuvat virrankuljetusominaisuudet eivät noudata mitään tunnettua mallia, mutta resisitiivisyyden lämpötilariippuvuutta kuvattiin onnistuneesti työssä kehitetyllä kahden spinkanavan mallilla. Lisäksi löydettiin näyttöä siitä, että energia-aukkoa enemmistö spinvyössä pienentävät virheet dominoivat resistiivisyyden lämpötilariippuvuutta SFMO ohutkalvoissa. Magnetoresistiivisyyden SFMO ohutkalvoissa havaittiin taas olevan yhdistelmä useita eri mekanismeja, jotka vaikuttavat olevan kytköksissä kalvojen rakenteellisiin muutoksiin.